Peran Perencanaan Sumber Daya Manusia dalam Mendorong Inovasi di PT Unilever Indonesia Tbk - Muhammad Iqbal Revilliano Trisandri; Rayhan Arief; Haykel Revelyn (Universitas 45 Surabaya, 2024)
This research aims to explore the role of human resource (HR) planning in driving innovation at PT Unilever Indonesia Tbk. The research method employs a qualitative approach. The data sources for this study include primary and secondary data. Data was collected through interviews with HR managers and employees, as well as the analysis of internal documents. The researcher utilized coding techniques for data analysis. The results indicate that effective HR planning strategies, including structured training programs and an inclusive organizational culture, contribute to increased employee engagement in the innovation process. Furthermore, the appropriate use of information technology has proven to enhance efficiency and support creativity. Despite challenges in communication and resistance to change, the findings suggest that good HR planning can create an environment conducive to sustainable innovation.